Theories bridging ethnography and evaluation : making transformative, intersectional, and comparative connections - Goodnight, Melissa Rae; Hopson, Rodney (Emerald Publishing Limited, 2024)
Theories Bridging Ethnography and Evaluation is the first of two volumes examining the connections between ethnography and evaluation in educational spaces. These volumes wrestle with pressing justice issues in today's societies while elucidating three themes--transformative, intersectional, and comparative--for guiding contemporary inquiry committed to realizing equity. Chapters situate inquiry in wide-ranging theories and the contested histories and policies of contexts--whether these spaces are globally, nationally, or locally defined. Exploring essential concepts (positionality, transparency, authenticity, and reciprocity), authors analyze the philosophical, methodological, relational, and ethical dimensions of the interconnected practice of ethnography and evaluation. Authors also highlight their own experiential learning: how these concepts are forged not only from literature but also from their lived experience of doing this transformative scholarship in the United States, Palestine-Israel, and India. Fusing interpretivist and transformative epistemologies, emphasizing both emic understandings and critical framings of social issues, Theories Bridging Ethnography and Evaluation draws upon social justice frameworks for conducting research and evaluation, including anti-racist, culturally responsive, and feminist theories.
Keywords: Educational evaluation.; Ethnology -- Research.; Education -- Evaluation & Assessment.; Education: examinations and assessment.; elektronické knihy; electronic books